2018
DOI: 10.1111/ijag.12342
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and structural investigations of xLi2O‐(1−x)Bi2O3 (0.25 ≤ x ≤ 0.35) glasses

Abstract: In this paper, we have studied the nonisothermal and isothermal crystallization kinetics of xLi2O‐(1−x)Bi2O3 (0.25 ≤ x ≤ 0.35) glasses, using differential scanning calorimetry. Both the energies of glass transition and crystallization are estimated, using the Ozawa and Kissinger methods for nonisothermal crystallization. The modified Johnson‐Mehl‐Avrami (JMA) equation is used to estimate the nature of nucleation and crystal growth during the nonisothermal crystallization. The nature of nucleation and crystal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…In general, the E g was higher than E c due to the molecular motion around the T g . A similar behavior was noted for lithium ions in bismuthate glasses .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In general, the E g was higher than E c due to the molecular motion around the T g . A similar behavior was noted for lithium ions in bismuthate glasses .…”
Section: Discussionsupporting
confidence: 71%
“…In general, the E g was higher than E c due to the molecular motion around the T g . 81 A similar behavior was noted for lithium ions in bismuthate glasses. 82 In this study, higher E x value was found compared to E c (see Figures 9 and 10) and this was attributed to the effect of bulk nucleation and crystal growth processes.…”
Section: Discussionsupporting
confidence: 62%